University Students' Knowledge and Perceptions Regarding the Nutrient Content of Plant-Based Beverages. (7th June 2021) - Hughes, Abigail; Hanson, Jennifer; Daniels, Elizabeth
Abstract: Objectives: While the consumption of milk in the U.S. continues to decline, plant-based beverages, like almond milk, are becoming increasingly popular. The purpose of this study was to assess university students' knowledge and perceptions on the nutrient content of plant-based beverages they consume. Methods: An online survey was used to collect responses from students at three U.S. universities. Responses were collected from February through September 2020. Students were asked to describe the type of plant-based beverage they drank most often. They were then asked to indicate whether they thought the beverage was greater than, less than, or equal to low-fat cow's milk with regard to energy, protein, vitamin D, and calcium content. Participants were instructed to respond without looking-up their answers, and they were given the option to select "I am not sure" as a response to each question. Using product nutrient labels, responses were scored for accuracy. Results: One hundred forty-four students who indicated they drank plant-based beverages completed the survey. Fifty-four % (n = 77) correctly rated the energy content of their beverage, 23% (n = 34) were unsure, 14% (n = 20) overestimated, and 8% (n = 11) underestimated the energy content. When asked about protein, 34% (n = 49) were unsure, 22% (n = 32) overestimated, 21% (n = 30) accurately estimated, and 2% (n = 3) underestimated their beverage's content. For calcium, 43% (n = 58) underestimated, 32% (n = 43) were unsure, 20% (n = 33) answered accurately, and 4% (n = 5) overestimated the content of their beverage. Lastly, for vitamin D, 38% (n = 50) were unsure, 38% (n = 50) underestimated, 23% (n = 30) were accurate, and 1% (n = 1) overestimated the amount of vitamin D in their plant-based beverage. Conclusions: Roughly half of all students had an accurate understanding of the energy content of the plant-based beverages they consume. However, the majority did not have an accurate understanding of their beverage's protein, vitamin D, or calcium content. Overall, students appeared to pay attention to the calorie content more than any other nutrient. Although more research is needed, the findings suggest the need to improve students' awareness of nutrition information and labeling in order to make informed beverage choices. Funding Sources: College of Health and Human Sciences, Kansas State University.